Repeatability of posterior and total corneal curvature measurements with a dual Scheimpflug–Placido tomographer. Issue 12 (December 2015) - Kim, Eric J.; de Oca, Ildamaris Montes; Wang, Li; Weikert, Mitchell P.; Koch, Douglas D.; Khandelwal, Sumitra S.
Abstract : Purpose : To evaluate the repeatability of the Galilei G4 dual Scheimpflug analyzer in measuring simulated keratometric, total, and posterior corneal curvature in normal and post‐refractive surgery eyes. Setting : Cullen Eye Institute, Baylor College of Medicine, Houston, Texas, USA. Design : Prospective evaluation of diagnostic technology. Methods : A single observer performed 3 consecutive measurements in 1 eye of each subject. The following were evaluated in both eyes and in eyes that had previous myopic excimer‐laser surgery: (1) simulated keratometric corneal power and astigmatism, (2) total corneal power and astigmatism, and (3) posterior corneal power and astigmatism. Repeatability was assessed by calculating the within‐subject standard deviation (Sw ), coefficient of variation (CoV), and intra‐class correlation coefficient (ICC). Results : The study evaluated 41 normal eyes and 36 post‐refractive surgery eyes. In normal eyes, the Sw was 0.08 diopters (D), 0.10 D, and 0.03 D for simulated keratometric, total, and posterior corneal power, respectively. The CoV ranged from 0.16% to 0.40%, and the ICC was 0.992 or more ( P < .001) for all corneal powers. In post‐refractive surgery eyes, the Sw was 0.09 D, 0.09 D, and 0.02 D for simulated keratometric, total, and posterior corneal power, respectively. The CoV ranged from 0.19% to 0.32%, and the ICC was 0.990 or more ( P < .001) for all corneal powers. For posterior corneal astigmatism, the ICC was 0.814 and 0.886 for normal and post‐refractive surgery eyes, respectively. Conclusions : In normal corneas and corneas that had undergone myopic excimer laser ablation, the dual Scheimpflug analyzer showed high intra‐observer repeatability for simulated keratometric, total, and posterior corneal power measurements and moderate repeatability for posterior corneal astigmatism. Financial Disclosure : Drs. Koch, Weikert, and Wang received research support from Ziemer USA, Inc. No other author has a financial or proprietary interest in any material or method mentioned.